The impact of intellectual capital performances towards bank’s profitibility – a study on Bank Rakyat Ayer Keroh / Nurul Akma Aznira Mat Yuni - Mat Yuni, Nurul Akma Aznira (2010)
The recent changes in the global economy, consisting of complex, dynamic and competitive environment have led to a difference between the modern approach of value creation and the traditional way of monitoring operations. In meeting these challenges of the new global economy, it leads to the importance of knowledge-based resources as the main factor in sustaining competitive advantage of the firms. The purpose of this study is to examine the intellectual capital performance and its relationship with financial performance of financial institutions in Malaysia for the period 2005 – 2009. This study is using exploratory and descriptive research design. A hypothesis testing is employed and it ready to test the hypothesis that already developed for this study. The value added intellectual coefficient (VAICTM) by Pulic is used. Moreover, the study is also use secondary data instead of primary data. This study does not cover all annual report of Bank Rakyat due to limited data. Future study should therefore further improve on the aspect of coverage. There are two types of analysis in SPSS program that had been used in the study to analyze the data correlation and regression. In addition, this studies also using Microsoft Excel to calculate the data. The paper reveals that VAIC and ROA are positively related among Malaysia’s finance sector. The results also show that the three components of VAIC are associated with profitability with the explanatory power of 7.4 per cent. The study is done in order to find the impact of intellectual capital performances towards bank’s profitability. Besides that, the study is also done to explain about the relationships of the factors; human capital, capital employed and structural capital.